PEMANTAUAN KEBOCORAN GAS DAN PANAS UDARA DENGAN METODE FUZZY BERBASISKAN IOT - Wicaksana, Dinar Anggit; Hirzan, Alauddin Maulana (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
The fuel commonly used by people for daily needs is Liquefied Petroleum Gas (LPG). LPG leaks can occur in closed spaces with temperatures above 30℃ because they contain very dangerous propane and butane compounds. If there is no early warning, the gas cylinder can expode and cause a major fire. The proposed model is capable of displaying gas concentrations and air heat (temperature and humidity) and reporting via telegram using the fuzzy mamdani algorithm. The aim of the research is to design a model for monitoring gas leaks and air heat. The sensors used in this system are tehe MQ6 sensor for gas detection, DHT22 for temperature and humidity detection, fire sensor, and nodeMCU as an Internet of Things-based processor using the fuzzy logic method. This system will turn on fan, buzzr and send a warning to telegram automatically when conditions are unsafe and dangerous. The conclusion of the research is that buzzer warning and telegram notifications make it easier for users to identify gas leaks so they can take immediate action